Improving Quran Memorization Through Digital Quran-Assisted Recitation and Recitation at MAN 1 Tuban - Aizatul Ulla; Sholikah (Konsultan Jurnal Ilmiah Indonesia, 2025)
Learning the memorization of the Qur’an (tahfidz) requires appropriate strategies to enable students to improve and maintain the quality of their memorization sustainably. This study aims to examine the improvement of students’ ability to memorize the Qur’an through the application of muraja’ah and takrir methods supported by a digital Qur’an at MAN 1 Tuban. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of muraja’ah and takrir, supported by the use of a digital Qur’an, is able to enhance students’ fluency, accuracy, and retention of Qur’anic memorization. In addition, the use of a digital Qur’an has a positive effect on students’ learning motivation and independence in memorizing the Qur’an. Therefore, it can be concluded that the integration of muraja’ah and takrir methods supported by a digital Qur’an is an effective learning strategy for improving students’ Qur’anic memorization ability at MAN 1 Tuban.